2017
DOI: 10.1177/1687814017720087
|View full text |Cite
|
Sign up to set email alerts
|

Research on crack initiation mechanism and fracture criterion of rock-type materials under compression–shear stress

Abstract: With the focus on the failure of single-cracked rocks under compression-shear stress, the form and the critical conditions of crack initiation by adopting theoretical derivation and numerical experiments methods are researched in this article. Maximum circumferential stress criterion and modified Griffith's criterion are utilized to derive the expressions for crack initiation angle and fracture criterion. Moreover, the PFC 3D , numerical simulation software, is used to verify the results of theoretical researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Despite of these weaknesses, this method was employed successfully by researches to investigate rock fracture and crack propagation (Fakhimi and Villegas, 2006;Hazzard et al, 2000;Konietzky et al, 2002;Lee and Jeon, 2011;Poulsen and Adhikary, 2013;Yue et al, 2017). based on relatively similar principles as PFC proposed by Frédéric and Magnier (1995) and Donzé and Magnier (1997).…”
Section: Bonded Particle Methodsmentioning
confidence: 99%
“…Despite of these weaknesses, this method was employed successfully by researches to investigate rock fracture and crack propagation (Fakhimi and Villegas, 2006;Hazzard et al, 2000;Konietzky et al, 2002;Lee and Jeon, 2011;Poulsen and Adhikary, 2013;Yue et al, 2017). based on relatively similar principles as PFC proposed by Frédéric and Magnier (1995) and Donzé and Magnier (1997).…”
Section: Bonded Particle Methodsmentioning
confidence: 99%
“…In any case, the obtained stress-strain curves are linear from the onset of loading and the estimated Young's modulus values correspond to the secant modulus at 50% of the peak strength (𝐸 50 ). In the case of uniaxial compression, crack initiation and peak load are very different (e.g., Yue et al 2017). This is due to the fact that, at low load level, a lot of microcracks start to develop in a diffuse manner, but later coalescence takes place and leads to a macroscopic crack and final failure.…”
Section: Model Geometriesmentioning
confidence: 99%
“…The crack propagation under uniaxial compression of a single fracture is taken as the research object. Cracks can be categorized as wing crack (Tw), anti-wing crack (To), coplanar shear crack (Sc) and oblique shear cracks (So) (Cao et al 2015;Yue et al 2017;Zhang et al 2014;Zhuang et al 2014), as shown in Fig. 3.…”
Section: Pattern Of Crack Propagationmentioning
confidence: 99%